RANCANG BANGUN INFORMASI POINT OF SALE MENGGUNAKAN FRAMEWORK CODEIGNITER PADA UMKM JASS COLLECTION - Tan, Steven; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2021)
The application of web-based information systems has been widely used today to help work in business activities and web-based systems are easy to access with various devices such as laptops, computers, cellphones and others. The recording of sales transactions at Jass Collection still often occurs when there are errors in writing code and product names and makes it difficult for cashiers to make sales reports that the owner will use to make decisions on adding stock of goods. The purpose of this research is To know how to design a point of sale information system with a codeigniter framework and and To find out how to implement a point of sale information system with a codeigniter framework. this research aims to design information systems point of sale l web-based Method used to build this information system is using the waterfall method,this web application can implemented in order help the store to manage sales.